Solution chemistry and anti-proliferative activity against glioblastoma cells of a vanadium(V) complex with two bioactive ligands - Levina, Aviva; Scalese, Gonzalo; Gambino, Dinorah; Crans, Debbie C.; Lay, Peter A. (Frontiers in Chemical Biology, 2024)
The current work demonstrated that a mixed-ligand vanadium coordination complex had high in vitro anti-proliferative activity against the human glioblastoma (T98G) cell line. The complex, [V V OL 1 L 2 ], contained two iron chelating ligands, 2-hydroxy-1-naphthylaldehyde isonicotinoylhydrazone (L 1 H2) and clioquinol (L 2 H) and was previously reported to be very effective against Trypanosoma cruzi, the causative agent of Chagas disease. These studies explored the possibility that a compound effective against Trypanosoma cruzi also is effective against human glioblastoma cancer cells even if the stability of the compound is limited. Since [V V OL 1 L 2 ] was poorly soluble in water and the clioquinol ligand dissociated from the complex upon addition to an aqueous environment, an understanding of the speciation chemistry was very important to explain its biological activity. The enhanced antiproliferative effects of the mixed-ligand vanadium complex against T98G cells could be due to either hydrolysis of complex and release of the toxic clioquinol, or the rapid uptake of the lipophilic complex prior to hydrolysis. The effects of speciation on the biological activity profile of the mixed-ligand complex were determined and compared to cellular uptake of vanadium and anti-proliferative efficacy of the complex. It was discovered that at least part of the potent toxicity of the mixed-ligand coordination complex stemmed from release of the bioactive clioquinol ligand from the complex. The studies described in this work show that the [V V (O)2(L 1 H)] coordination complex was the most potent complex that remained intact and, hence, the complex that is the most biological active. Thus, future development of complexes should focus on the one-ligand intact complexes or making any mixed-ligand complex more water soluble, stable in aqueous solution, or designed to be rapidly taken up by diseased cells prior to hydrolysis.